Clinical efficacy and safety of ultra-short-course chemotherapy in treatment of spinal tuberculosis after complete debridement: an observational study. Issue 2 (February 2021) - Sun, Guangwei; Wang, Qian; Liang, Qiang; Song, Xiangwei; Chen, Jian; Shi, Jiandang; Ma, Wenxin; Yuan, Hucheng; Jin, Weidong; Wang, Zili
Abstract: Objective: To evaluate the clinical efficacy and safety of ultra-short-course chemotherapy (<4 months) in treating spinal tuberculosis following complete debridement. Methods: Clinical data of patients diagnosed with spinal tuberculosis, who underwent surgery with postoperative chemotherapy for < 4 months at the General Hospital of Ningxia Medical University between January 2005 and March 2015, were retrospectively analysed. Clinical manifestations, American Spinal Injury Association grades, states of bone fusion and lesion healing, deformity correction, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) levels and adverse drug reactions, observed before and after surgery and at the final follow-up, were assessed. Results: Sixty patients were included, comprising 26 male and 34 female patients aged 16–78 years (mean, 40.85 years). Patients received postoperative chemotherapy for 3–4 months (mean, 3.61 months) and were followed for 25–129 months (mean, 70.61 months). Spinal tuberculosis recurred after surgery in one patient, who was cured by subsequent surgery. At the final follow-up, no symptoms of tuberculosis, local pain, abscess or sinus were observed. Daily life and working abilities were almost recovered in all patients. ESR and CRP levels were restored to normal, bone grafts fused, lesions healed and neurological functions were recovered. Postoperative chemotherapy-induced complications occurred in 10 patients (16.67%). Conclusions: Complete debridement plus ultra-short-course chemotherapy for 3–4 months may be safe and efficacious in treating spinal tuberculosis, and requires further investigation.